Transitional mutations increase to mitigate the bias effect on the X chromosome inactivation that leads to the onset of mutations with pathological effects in the gene for iduronato2 sulphatase (IDS) (3.1.6.13) (Revista de Investigaciones Universidad del Quindío, 2017)
Several authors have reported the role of DNA methylation on IDS gene as a possible explanation of X chromosome inactivation. Besides, patients who suffer from mucopolysaccharidosis show a skewed X chromosome inactivation pattern related to a low or none iduronate-2-sulfatase activity. We reported a consisted pattern of transitional mutation c.438C>T on relative females of MPS II patients due to point mutations c.641C>T, and c.1122C>T. From several bioinformatics analysis we found an association between the inherited deamination mechanisms, responsible to avoid skewed X inactivation, and transitional mutations on pathogenic spots along IDS gene. Besides, data analysis predicted a possible increasing on pathogenic mutations on IDS gene. We consider this finding very valuable to propose a broad screening on fertile females of methylation target spots in X chromosome. Results from these screening test would help to prevent allele frequency increasing on X linked diseases as MPS, Lesch-Nyhan syndrome, and Duchenne muscular dystrophy.
Keywords: Gen IDS; Mucopolysaccharidosis; mutations; chromosome X